The impact of terrain on lower limb bone structure. Issue 4 (16th February 2019) - Holt, Brigitte; Whittey, Erin
Abstract: Objectives: Lower limb diaphyseal geometry is often used to evaluate mobility in past populations. Diaphyseal dimensions such as high shape ( I X / I Y ) indices generally thought to reflect high mobility may also result from walking over rough terrain. This study investigates the possible effects of terrain on lower limb diaphyseal cross‐sectional geometric dimensions. Materials: The sample ( N = 3, 195) comprises adult skeletons from Europe, Africa, North America, and Asia, spanning from around 30, 000 BP to mid‐twentieth century. Methods: Femoral and tibial shape and bending/torsional strength dimensions were gathered either as part of a previous project or were generously provided by researchers. Local terrain for each site was quantified with ArcGIS mapping software using geographic coordinates and USGS elevation data, and characterized as flat, hilly, or mountainous. Results: Analysis of variance shows significant differences ( p < .05) in midshaft femoral and tibial shape ratio and relative bending/torsional strength among the three terrain categories, with more AP oriented diaphyseal shapes and greater relative strength in hilly and mountainous groups, even after correcting for the effect of subsistence. As expected, the impact of terrain is much more marked for hunter‐gatherers and agriculturalists than for more mechanized recent populations. Interestingly, the effect of terrain is confounded in higher latitude individuals that exhibit increased ML bending strength, probably reflecting larger body breadth. Discussion: This study underscores the mechanical significance of traveling over rough terrain and highlights the complex interactions of mobility, terrain, and body shape that contribute to shaping lower limb bone diaphyseal structure.